Male professional footballers' use of mental skills training and counselling: Dilemma or conundrum?. Issue 4 (30th July 2021) - Abela, Daniel; Falzon, Ruth; Muscat, Adele
Abstract: Background: The study explores male footballers' experiences of Mental Skills Training (MST) – usually carried out by sports psychologists, and counselling (Herzog & Hays, 2012). Method: This research's aim begged a qualitative approach – interpretative phenomenological analysis. Semi‐structured, audio‐recorded interviews were used with seven participant‐footballers. Findings: Participants faced a number of unique challenges throughout their career and consider support pivotal for their success in the industry. Parental and institutional support were key sources for support. Participants experienced counselling as a safe and reliable space, where the therapeutic relationship extended beyond football‐related issues. Participants explained that MST can be self‐taught, is a direct hands‐on approach, can be practised whilst injured, and a first point of contact with other services and forms of therapeutic support. Views on their expectations of MST and counselling services varied: either compatible and should be delivered by the same person, or different and should delivered separately. Participants identified others' perceptions as possible challenges for footballers accessing MST and counselling. Recommendations: Participants recommended further research with other athletes, with footballers from diverse countries and cultures, with other helping professionals, with leaders, with managers and sponsors of football, and with sports in general. Participants suggested counsellor‐training in sport psychology, sports psychologists and counsellors' participation in sporting contexts, and developing working relationships with kindred professions. They also argued for awareness campaigns with the general public and with stakeholders. An amendment to the local national policy should incorporate mental and social well‐being of athletes as a priority for sporting institutions.